Implementation of the Time Token Arends Learning Model in Speaking Skills in Class V of Elementary Schools - Suriani, Ari; Hanum, Zikra; Sukma, Elfia; Habibi, M; Chandra, Chandra (Universitas Trunojoyo Madura, 2024)
The aim of this research is to find out how the Time Token Arends learning model is implemented in speaking skills in elementary schools. This research uses a qualitative approach and qualitative descriptive research methods. This observation was carried out in an elementary school with a class V representative population of 20 students and consisting of 11 female students and 9 male students. The instruments used in the research are divided into 3 parts, namely; observation guide, interview guide and documentation study. The results of this research show that the learning process that has been used so far has been implemented well and smoothly. The Time Token Arends learning model in the learning process in elementary schools is carried out by forming groups, giving group assignments in the form of questions, and all groups are directed to participate in group activities (discussions).